CHLOROMENITE, CU9O2(SEO3)4CL6, A NEW MINERAL FROM THE TOLBACHIK VOLCANO, KAMCHATKA, RUSSIA - Vergasova L.; Ananiev V.; Krivovichev S.; Semenova T.; Filatov S. (My University, 1999)
Chloromenite, ideally Cu9O2(SeO3)4Cl6, was found in a fumarole in the North Breakthrough of the Great Fissure Tolbachik eruption (1975-76, Kamchatka Peninsula, Russia). It occurs as transparent, tobacco-green crystals, tabular on {101}, elongated in [111] and [111], rarely in [010]; well-developed forms are {001}, {101}, {101}, {110}, {011}, {312}; forms {301}, {310} are poorly-developed. Associated minerals are melanothalite, an unknown scaly mineral, an unknown Se-containing mineral and weathering products. Chloromenite is plastic and has a perfect cleavage on (101), a strong vitreous luster and a yellowish-green streak. H = 27 kg/mm2. The mineral is biaxial, optically negative; α = 1.87(1), β = 1.92(1), γ = 1.94(1), 2V(means) = 66(2)°, 2V(calc) = 63°; orientation: Y = β, Z ~ γ. Pleochroism is clear in the green tones: α - green, β - light brownish-green, γ - black brownish-green. Chloromenite is monoclinic, space group 12/m, a = 14.11(1), b = 6.274(2), c = 13.00(1) Å, β = 113.0°(1), V = 1059 (2) Å3, Z = 2, D(x) = 4.15(1) g/cm3. The diagnostic lines of the X-ray powder diffraction pattern are (I-d-hkl): 63-11.3-101; 21-7.49-101; 17-6.51-200; 83-5.56-011; 100-3.45-103; 39-3.24-204; 33-2.71-503,312; 61-2.49-303,402. The crystal structure was solved by direct methods and refined to R = 0.051 (wR = 0.128). There are five copper positions in the chloromenite structure that correspond to five crystal chemically distinct coordination polyhedra: Cu(1), Cu(5) - the squares [2O + 2Cl] and [4O], Cu(2), Cu(4) - trigonal bipyramids [4O + Cl] and [5O], respectively, Cu(3) - a flattened tetrahedron [2O + 2Cl]. The structure is based on heteropolyhedral sheets parallel to (101) and composed of the [Cu(2)O4Cl], [Cu(5)O4] and [Cu(1)O2Cl2] coordination polyhedra. The bipyramids [Cu(2)O4Cl] are linked through edges with two [Cu(5)O4] and one [Cu(1)O2Cl2] squares. The sheets are linked together through the [Cu(4)O5] bipyramids and the [Cu(3)O2Cl2] tetrahedra. Microprobe analysis gave the following chemical composition (wt %): CuO 46.23 (45.33-46.83), ZnO 5.94 (5.76-6.03), SeO2 34.37 (33.48-35.56), Cl 16.57 (16.30-17.08), O = Cl2-3.74 (3.68-3.85), Σ 99.36 (98.90-99.69). The empirical formula, calculated from O + Cl = 20, Cu7.71Zn0.97Se4.11O13.80Cl6.20, is close to the ideal one, Cu9O2 (SeO3)4Cl6, confirmed by the crystal structure analysis. The name chloromenite is chosen in accord with colour and chemical composition: χλωπoζ - < > (this also indicates that the mineral contains Cl) and μηvαζ - < > (this indicates that the mineral contains Se).